A Proposal for an Accelerated Evaporation Treatment System for Alumina Industrial Soda Ash Wastes and Feasibility of the use Soda Ash and Sodium Percarbonate for Co2 Capture and Phenol Oxidation in Water (Global Journal of Science Frontier Research, 2018)
Increasing interest in CO 2 sequestration is linked to the need for cost-effective alternatives of In Situ Combustion Pilot Projects (ISCPP) which is an ongoing field testing effort aimed at assessing its efficacy in increasing the recovery factor of heavy oil reservoirs from Hugo Chávez Orinoco Oil Belt (Venezuela). A proposal is presented for an accelerated evaporation system for volume decreasing of caustic liquor in alumina industrial artificial lagoons, obtaining sodium carbonate (soda ash) and its later utilization in the synthesis of sodium percarbonate (Na 2 CO 3 •1.5H 2 O 2 ) (SPC). The caustic liquor evaporation rate was of 0.146 mm/h using only radiation in the evaporation system. When only artificial wind was used the evaporation rate was 0 .196 mm/h, which means an increase of 34% in the evaporation rate.
Keywords: by-products (caustic liquor “soda ash” and red mud); bayer process; in situ combustion; mineral carbonation; sodium percarbonate (SPC)